ANALISIS DAERAH RAWAN KECELAKAAN LALU LINTAS (STUDI KASUS JALAN NASIONAL ARTERI PRIMER DAN ARTERI SEKUNDER KABUPATEN KENDAL) - Al Qurni, Isa (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
This study aims to determine the characteristics of the accident-prone areas (black site) and points prone toaccidents (black spot) traffic, the location of the accident-prone areas (black site) and points prone toaccidents (black spot) traffic, and map location of accident-prone areas (black site) and accident-pronepoints (black spot) traffic. The variables in this study using primary data and secondary data. Primary dataincludes determining the coordinates of X and Y, land use, and traffic signs. The secondary data includesgeometric road, traffic volume, road capacity, the data event of an accident, and the slope of the terrain.Mechanical analysis identifying accident-prone areas (black site) and accident-prone points (black spot)traffic is Z-Score analysis techniques and Cusum (Cumulative Summary). The results showed that thecharacteristics of the accident-prone areas (black site) and accident-prone points (black spot) traffic isinfluenced by land use, geometric road, traffic volume, the capacity of the road, traffic signs, and the datascene of the accident.